Axial compression characteristics of rubberized geopolymer concrete column - Azunna, Sunday U.; Aziz, Farah N.A.A.; Rashid, Raizal S.M. (Elsevier, 2025)
Rubberized concrete has, over the years, proven to be a concrete that is more beneficial to the environment than nominal concrete, as it helps to reduce the menace of waste disposal and possesses higher impact resistance. Geopolymer concrete is another economical concrete that uses industrial byproducts, thereby reducing the emission of carbon. Rubberized geopolymer concrete (RuGPC) combines both concrete advantages, and it is important to comprehend its structural performance to promote its application for construction purposes. This study's objective is to examine the effects of using crumb rubber (CR) as a partial replacement for fine aggregate on the axial compression characteristics of geopolymer concrete columns. To achieve this, three batches of concrete containing CR at 0 %, 10 %, and 20 % replacement of fine aggregate were prepared to produce six short RuGPC short columns. These columns are subjected to an axial compression test where axial and lateral deformation are recorded. The results indicated that compared to the control specimen, the axial load capacity and stiffness of 20 % RuGPC columns decreased by 17.5 % and 43.58 %, respectively. Conversely, axial deformation, lateral deformation, toughness, and the ductility index increased by 46.09 %, 55.84 %, 30.75 %, and 19.63 %, respectively. Existing standards for normal concrete were inconsistent in their prediction of the column's axial load capacity. For that reason, a numerical model was proposed for predicting the axial load capacity of RuGPC columns, which accurately reflected the experimental results, with a standard deviation and coefficient of variation of 0.04 and 3.72 %, respectively. Thus, the numerical formula can be utilized to predict the axial capacity of RuGPC columns with a high degree of accuracy and minimal error. The energy absorption qualities of RuGPC column make it suitable for structures subject to seismic and cyclic loads.